Parcel Hub for UTHM Residential College Management System - MOHAMAD ZAN, NOOR AISYAH; Mohamad Aizi Salamat, (Applied Information Technology And Computer Science, 2025)
Logistics management is a process of organizing and supervising the movement of goods and products. Effective management of package logistics is crucial for the smooth functioning of educational institutions and ensuring secure operations, particularly in busy residential college settings. Nonetheless, the service center of UTHM Residential College is using a traditional procedure throughout their logistics operations. The current manual approach presents issues in terms of security, tracking, and misplaced package due to the growing volume of package and deliveries. Therefore, the development of a new system hopefully can solve the problem and can be more efficient than before. The proposed system will assist students receive real-time notifications so they can pick up shipments as soon as possible. Administrative staff will benefit from automated data entry since it will improve record-keeping and reduce errors. By leveraging advanced technologies and a user-friendly interface, the Parcel Hub system will enhance the overall efficiency of the parcel management process. This report outlines the conceptual framework, development methodology, and technology stack utilized in the creation of the Parcel Hub system. System Development Life Cycle Prototyping model is used as the methodology to develop this system and using PHP as server-side scripting. As a result, the project development benefits for emphasizing student information management, package receipt and delivery information to meet a systematic and efficient management of the UTHM Residential College System.